Telecommunication Infrastructure Development and FDI into Asian Developing Nations - DR. MUMTAZ HUSSAIN SHAH; FAISAL KHAN (Journal of Business & Tourism, 2021)
This study strives to evaluate the effects of infrastructure availability and development on foreign direct investment (FDI) in host developing nations.Employing fixed effects panel estimation technique, panel data for 23 Asian developing countries, from 1990-2009 is used with heteroscedasticity corrected standard errors. The results reveal a strong favourable impact of telecom infrastructure (measured by mobile subscriptions) in drawing inward FDI. Therefore, it is concluded that a country with improved infrastructure in general and telecom infrastructure in particular is likely to pull in more FDI. Other variables such as market size, economic development, and currency valuation (measured by exchange rate) appear important in captivating multinational investors, as they exhibit significant coefficients. On the contrary, high-inflation significantly deters inward FDI.